(untitled) (Географический вестник=Geographical bulletin, 2017)
Представлено состояние гидротехнических сооружений Пермского края на 1 января 2010 г. По результатам инвентаризации сооружений, выполненной ОАО «Пермгипроводхоз», выявлена ведомственная принадлежность большинства объектов. Установлены сооружения, требующие капитального и текущего ремонта, а также реконструкции. CONDITION OF HYDRAULIC ENGINEERING CONSTRUCTIONS OF PERM REGION (BY 1st JANUARY, 2010) Condition of hydraulic engineering constructions of Perm region by January, 1st, 2010 is presented. By results of the inventory of constructions executed by Open Society "Project institute of a water management", the departmental accessory of the majority of objects is revealed. The constructions demanding capital and operating repair, and also reconstruction are established.